Η ρητορική υπέρ της θρησκευτικής ανεκτικότητας: ο Λόγος 30 «πρὸς Θεοδόσιον τὸν βασιλέα ὑπὲρ τῶν ἱερῶν» του Λιβανίου. - ΠΟΛΥΖΟΣ, Σωτήριος Σ. (Byzantina Symmeikta, 2023)
The present article discusses how the Antiochean orator Libanius endeavors to create through his rhetoric a more tolerant stance towards the already persecuted paganism and its cults in the later 4th century during the reign of emperor Theodosius I. By tracing and interpreting the rhetorical techniques which the orator uses in the Oration 30 (Pro Templis) so as to achieve his goal, the article also presents the religious unrest that broke out in the broader area of Coele Syria due to the gradual criminalization of the pagan cults and the plundering of pagan shrines and temples by highranking Christian officers and fervent monks. Libanius tends to become not only a pagan apologist, but he also seems to assume a role of defender of the social stability and order, by calling for religious neutrality (and subsequently tolerance) in the public sphere, which was dominated by the Nicene Christianity.